2008
DOI: 10.1097/wco.0b013e3282fe205b
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric headache

Abstract: A comprehensive management approach blending the most current acute, preventive, and biobehavioral treatments will be reviewed. Further research, with novel study designs, in pediatric headaches is needed to help reveal additional pathophysiological mechanisms, improve diagnostic criteria, and advance optimal treatment. Prospective studies are needed to fully evaluate the efficacy of preventive management in this population and to establish whether early intervention might slow this disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…This is not only because of the inability of childred to describe their symptoms (13), but also because of the greater tendency at this age for the headache pattern, and thus the diagnosis, to change over time (14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…This is not only because of the inability of childred to describe their symptoms (13), but also because of the greater tendency at this age for the headache pattern, and thus the diagnosis, to change over time (14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…One of the limitations related to the use of ICHD-II criteria in the diagnosis of pediatric migraine is the difficulty children encounter in describing the features of headache and any associated symptoms. Moreover, as the features of headache may change from preschool age to adolescence [4], some authors have suggested modifying the criteria for headache diagnosis in childhood [5]. …”
Section: Introductionmentioning
confidence: 99%
“…5,6 A revised classification should also account for the recent observation that headache characteristics change over time from preschool age to puberty. 7…”
Section: Table 2 Migraine Without Aura In Children (Ichd-ii Diagnostmentioning
confidence: 99%